Computation on Bio-Informatics - Naga, Shubham; Choudhary, Sapna (International Journal of Computer Sciences and Engineering, 2025)
Bioinformatics is an interdisciplinary field mainly involving molecular biology and genetics, computer science, mathematics, and statistics. Data intensive, large-scale biological problems are addressed from a computational point of view. The most common problems are modelling biological processes at the molecular level and making inferences from collected data. As an emerging discipline, it covers a lot of topics from the storage of DNA data and the mathematical modelling of biological sequences, to the analysis of possible mechanisms behind complex human diseases, to the understanding modelling of the evolutionary history of life, etc. It studies the DNA and genetic information.